2022
DOI: 10.1111/jan.15226
|View full text |Cite
|
Sign up to set email alerts
|

Working with or against the system: Nurses' and midwives' process of providing abortion care in the context of gender‐based violence in Australia

Abstract: Aims:The aim of this study was to explain the process through which Australian nurses and midwives provide abortion care to people affected by gender-based violence (GBV). Design:A constructivist grounded theory study. Methods:This study took place between 2019 and 2021. The lead author conducted semi-structured interviews with 18 Australian nurses and midwives who provided abortion care. Participants were recruited through pro-abortion, nursing and midwifery networks using a snowballing technique. Data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 55 publications
1
2
0
1
Order By: Relevance
“…These acts ranged from arguably mundane and avoidant acts to more confrontational, public, and even illegal acts. These findings show a number of similar forms of action, identified by Shaw, and colleagues ( 2018 ) like verbal challenges and modelling behaviours and Mainey et al ( 2022 ) like subversion as a means to place patient interests first. While no participants discussed “doctoring” documents, parallels can also be found with Shutzberg ( 2019 ) and other work that has explored how health workers have responded to bureaucratic and managerial encroachments into clinical care; in this study participants utilized a variety of tactics to navigate and undermine systems and structures that would otherwise harm health or undermine their clinical judgement; beyond this however, participants also reported a wide range of actions and motivations.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…These acts ranged from arguably mundane and avoidant acts to more confrontational, public, and even illegal acts. These findings show a number of similar forms of action, identified by Shaw, and colleagues ( 2018 ) like verbal challenges and modelling behaviours and Mainey et al ( 2022 ) like subversion as a means to place patient interests first. While no participants discussed “doctoring” documents, parallels can also be found with Shutzberg ( 2019 ) and other work that has explored how health workers have responded to bureaucratic and managerial encroachments into clinical care; in this study participants utilized a variety of tactics to navigate and undermine systems and structures that would otherwise harm health or undermine their clinical judgement; beyond this however, participants also reported a wide range of actions and motivations.…”
Section: Discussionsupporting
confidence: 70%
“…Beyond these examples, resistance in the workplace takes more diverse forms and is motivated by a range of issues. In Australia, Mainey, O’Mullan, and Reid-Searl ( 2022 ) found that nurses who provided abortion care undermined laws, systems and individuals who sought to impose barriers on access to abortion. Such acts also occur in far less politically charged settings, for example a body of work by Shutzberg ( 2019 ) explored strategies employed by Swedish GPs to increase the likelihood that patients’ sickness certificate would be approved by the Swedish Social Insurance Agency.…”
Section: Introductionmentioning
confidence: 99%
“…Os resultados da pesquisa mostraram que as participantes não se sentiam adequadamente preparadas, durante o período de formação graduada, para o atendimento das usuárias que buscavam o aborto, tendo havido necessidade de estudos complementares. As autoras da pesquisa também sugerem que a ausência de qualificação dos profissionais sobre o tema pode explicar a revitimização das usuárias pelo sistema de saúde (8) .…”
Section: Introductionunclassified
“…The professional obligation to provide person-centred care was a higher priority than following the official or unofficial rules of the organisations. 19 The second phase study turned the focus from individual action to the organisational environment. We found that participants believed that patients are 'mostly uncatered for'.…”
Section: Introductionmentioning
confidence: 99%